Penyusunan E-Modul Pelatihan BIM pada Jabatan Kerja Juru Gambar BIM Jenjang 3 Berbasis SKKNI No. 3 Tahun 2023 - Adelia, Lusieta; Widiasanti, Irika; Maulana, Arris (LPPM Institut Pendidikan Nusantara Global, 2025)
This research aims to develop training materials for Competency-Based Training E-Modules for Level 3 BIM Draftsman in accordance with SKKNI No. 3 of 2023. The research was conducted using the Research and Development (R&D) method of the 4D model which includes four main stages: (1) Define, (2) Design, (3) Development, and (4) Dissemination. Data collection techniques were carried out with questionnaires as an instrument of feasibility assessment by three material experts, three media experts, and users, additionally pre-test and post-test to measure effectiveness in the limited trial phase of e-module development. Data analysis techniques used in this study include descriptive qualitative for expert suggestions and descriptive statistics for quantitative data analysis from expert feasibility, content validity, and user assessment. The results showed that the level 3 BIM draftsman training e-module achieved a feasibility score of 94% from material experts and 96% from media experts, both categorized as “Excellent” category. Furthermore, the content validity analysis using Aiken's V resulted in scores of 0.93 for material experts and 0.95 for media experts, both classified as